Can Nd:YAG laser irradiated on dentin with non-polymerized adhesives influence the durability of bond strength and micromorfology of hybrid layer? - Barcellos, Daphne Camara; Batista, Graziela Ribeiro; Persici, Erasmo de Sousa; Pucci, César Rogério; Huhtala, Maria Filomena Rocha Lima; Gonçalves, Sérgio Eduardo de Paiva (Brazilian Dental Science, 2016)
Objective: This study evaluated the durability of bond strength to dentin using total-etch (Single Bond /SB) and self-etch (Clearfil SE Bond/CSEB) adhesives associated with Nd:YAG Laser irradiation through the unpolymerized adhesives. Also, this study evaluated micromorfological chances in hybryd layer after 12 months wter storage.Material and Methods: Bovine incisors were worn to expose a dentin area and were divided into 4 groups (n = 15):Group 1 (Control) – SB + photopolymerization; Group 2 (Control) – CSEB + photopolymerization; Group 3 (Experimental/Laser) - SB + Nd:YAG laser (149.28 J/cm2) + photopolymerization; Group 4 (Experimental/Laser) – CSEB + Nd:YAG (149.28 J/cm2) + photopolymerization.Composite blocks were fabricated; intact teeth were stored for 24 h or 12 months (12 m), sectioned into beams and submitted to microtensile bond strength tests.Two teeth from each group (n = 2) were prepared for SEM analysis. Results: Results were analyzed by three-way ANOVA (adhesive, Technique and storage time) and Tukey tests (0.05). Results: For interaction Adhesive X Technique X Storage time the mean values (MPa) were:SB/Control/24h = 34.05(±6.14)a; CSEB /Control/24h = 32.12(±5.26)a; SB/Laser/24h = 30.54(±5.94)a; CSEB/Laser/24h = 29.45(±5.11)a; SB/Control/12m = 29.36(±5.57)a; CSEB/Control/12m = 29.09(±8.84)a; SB/Laser/12m = 22.06(±3.77)b; CSEB/Laser/12m = 13.35(± 3.35)c. Conclusion: SEM showed evident areas of micromorphological alterations on lased samples after 12 months water storage with accelerated degradation of the hybrid layer.Bond strength decreased when dentin irradiated with the Nd:YAG laser through unpolymerized adhesives was stored in water for 12 months.Laser irradiation of dentin through unpolymerized self-etch adhesive significantly reduced bond strength when compare with total-etch adhesive after 12 months water storage. Keywords:Dental adhesives; Dentin bonding; Nd yag; Tensile strength.